Bisimulations of boolean control networks with impulsive effects and its application in controllability. Issue 6 (9th May 2019) - Zhang, Qiliang; Feng, Jun‐e; Wang, Biao; Meng, Min
Abstract: This paper addresses the bisimulations of Boolean control networks (BCNs) with impulsive effects. First, by analyzing the state transitions of BCNs with impulsive effects, a necessary and sufficient condition for bisimulations is obtained. Second, by virtue of bisimulations, a premise for propagating complete controllability is proposed. Then, the structure characteristics of BCNs with impulsive effects propagating complete controllability are presented. Finally, two illustrative examples are provided to demonstrate the validity of the obtained results.